Parliaments and the European Court of Human Rights - Leach, Philip (Philip Royston); Donald, Alice (Oxford : Oxford University Press, 2016)
Through empirical assessment of the role of the parliaments of the UK, the Netherlands, Germany, Ukraine, and Romania, this book addresses the theme of how engaged parliaments are and should be, in the implementation of judgments of the European Court of Human Rights.
Previously issued in print: 2016.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on August 8, 2016).
Keywords: European Court of Human Rights; Legislative bodies -- Europe; Law; International law